Aggregation and micellization of sodium dodecyl sulfate in the presence of Ce(III) at different temperatures: A conductometric study - Valente, Artur J. M. (2008)
Aggregation properties of sodium dodecyl sulfate (SDS) in the presence of cerium(III) chloride, at various temperatures (298.15-323.15 K) have been measured by the electrical conductance technique. The experimental data on aqueous solutions as a function of SDS concentration show the presence of two inflexion points indicating the presence of two distinct interaction mechanisms: the first, occurring at SDS concentrations below the critical micelle concentration of the pure surfactant, which can be explained by the formation of aggregates between dodecyl sulfate (DS-) and Ce(III), while the second one, at SDS concentrations around the critical micelle concentration (cmc) of the pure surfactant which is due to the SDS micellization. The aggregation between DS- and Ce(III) was confirmed by static light scattering. The binding ratio of DS-/Ce(III) changes from 6 to 4, shows a slight dependence on the Ce(III) concentration and is independent of the temperature. The thermodynamic micellization parameters, Gibbs energy, enthalpy and entropy of micellization were calculated on the basis of the experimental data for the aggregation concentration, and the degree of counterion dissociation of the micelles. The SDS micellization is energetically favoured by increasing either the concentration of CeCl3 or the temperature. Such behaviour is clearly dominated by a decrease of the micellization (exothermic) enthalpy. The entropy of micellization approaches zero as the cerium(III) chloride concentration and temperature increase.